Study of Corrosion in Biocompatible Metals for Implants: A RevieW - Manam, N.S.; W. S., Wan Harun; Awang Shri, Dayangku Noorfazidah; Saiful Anwar, Che Ghani; Kurniawan, Tedi; M. H., Ismail; M. H. I., Ibrahim (Elsevier Ltd, 2017)
High requirements in biomedical applications are yet to be met, equally in joint and bone substitution and the healing and renewal of bone weaknesses. The compatibility with the human body is the main precondition for the choice of biomaterials, which should thus have some significant properties that will be durable for use in the body without rejection. This paper concentrates, especially, on biocompatible metals, although there are also biomaterials made of polymers, ceramics, and composite materials. Considerations in selecting materials for biomedical applications such as biocompatibility, the high corrosion and wear resistance, and osseointegration are discussed. This paper reviews the applications of three main types of biocompatible metal, namely, stainless steels, cobalt-chromium alloys, and titanium and its alloys. The corrosion resistance of each alloy is in focus. It can be confidently declared that biocompatible metals will continue to be used as biomaterials in the future with further improvements and new revolutionary bio-functionalities in the use of metals.